Characterization of an Antibody Depletion Assay for Analysis of Bactericidal Antibody Specificity - Zollinger, Wendell D. (American Society for Microbiology (ASM), 2009)
Serum bactericidal antibodies are important for protection against systemic Neisseria meningitidis infections. Consequently, identifying the specific targets of bactericidal antibodies is important for understanding protective immunity to meningococcal disease and for vaccine development and evaluation. We have developed a new assay that can be used to investigate the specificity of serum bactericidal antibodies. Prior to testing for bactericidal activity, antibodies specific for a given antigen or group of antigens are depleted from a serum sample by incubation with the antigen(s) bound to the wells of a 96-well microplate. A dilution series of the antigen is bound to the plate to assess the effectiveness of the antigen in removing the bactericidal antibodies. Removal of antibodies with solid-phase antigen prior to bactericidal testing avoids depletion of complement by soluble immune complexes that can form when soluble antigen is present in the bactericidal test mixture (direct inhibition). The parameters associated with this assay are investigated and compared with those associated with a direct-inhibition assay. The bactericidal depletion assay can be an effective tool for studying the specificity of serum bactericidal antibodies.